A sulfur-resistant low-temperature carbon-based denitrification catalyst and its preparation method and application

By uniformly distributing MnO2, Fe2O3 and CeO2 active components on the modified activated carbon support, combined with the acid solution oxidation modification and segmented calcining process, the existing low-temperature denitrification catalysts have been solved, and high efficiency has been achieved. Low-cost low-temperature flue gas denitrification effect.

CN118491534BActive Publication Date: 2024-12-24이너 몽골리아 일렉트릭 파워 그룹 컴퍼니 리미티드 이너 몽골리아 일렉트릭 파워 리서치 인스티튜트 브랜치

Patent Information

Application Number
CN202410964713.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-18
Publication Date
2024-12-24
Estimated Expiration
2044-07-18

AI Technical Summary

Technical Problem

The existing low-temperature denitrification catalysts have low denitrification efficiency and poor sulfur resistance in the low-temperature stage, resulting in many restrictions when using the catalyst. The preparation method has problems such as high loading of active components, high consumption of chemical reagents, and high cost.

Method used

Modified activated carbon is used as the support and MnO2, Fe2O3 and CeO2 are supported as active components. The active components are evenly distributed through the acid solution oxidation modification and segmented calcining process to improve the low-temperature denitrification efficiency and sulfur resistance of the catalyst.

Benefits of technology

It significantly improves the low-temperature denitrification efficiency and sulfur resistance of the catalyst, extends the service life of the catalyst, reduces the preparation cost, and realizes low-temperature flue gas denitrition under SO2 atmosphere, which is suitable for low-temperature SCR denitrition systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118491534B_ABST
    Figure CN118491534B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of flue gas denitration, and in particular to a sulfur-resistant low-temperature carbon-based denitration catalyst and its preparation method and application. The catalyst is a loaded catalyst with modified activated carbon as a carrier and a metal composite oxide as an active component; the metal composite oxide includes MnO2, Fe2O3 and CeO2, wherein the mass percentages of MnO2, Fe2O3 and CeO2 in the total mass of the catalyst are 6.0-8.0%, 0.5-1.5% and 0.3-1.0%, respectively. The catalyst of the present invention has good sulfur resistance, good pore structure, rich oxygen-containing functional groups, recyclable regeneration, and Mn / Fe / Ce active component NO x It has the advantages of excellent reduction performance, and can have a good denitrification effect at low temperature (100-220℃), and realize low-temperature flue gas denitrification of composite carbon-based catalysts in SO2 atmosphere, and the service life of the catalyst is extended.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of flue gas denitration, and in particular to a sulfur-resistant low-temperature carbon-based denitration catalyst and a preparation method and application thereof. Background Art

[0002] Nitrogen oxides (NO x ) is one of the important pollutants that cause acid rain, react with hydrocarbons to form photochemical smog, increase near-ground ozone concentration and other atmospheric pollution problems, which can cause a series of environmental problems and endanger human health. x Emission reduction technology has always been the focus of attention of all countries. Ammonia selective catalytic reduction (NH3-SCR) is the current mainstream flue gas denitrification and NOx emission control technology. That is, under the action of a catalyst, an amino reducing agent (ammonia, ammonia water, urea, etc.) is injected to reduce NO in the flue gas. x Reduced to N2, the core of this technology is the denitrification catalyst, and its performance is directly related to the overall denitrification efficiency.

[0003] Commercial NH3-SCR catalysts are mainly V2O5-TiO2 and V2O5-WO2(MoO2)-TiO2 series catalysts, which show high NO x removal rate and good sulfur resistance. However, V2O5 is a highly toxic substance, which is prone to chemical poisoning, pore blockage, abrasion and other defects during the reaction process, which not only reduces the activity of the catalyst, but also threatens human health. At the same time, since the flue gas temperature in the non-electric industry is generally low (140-300℃), which is far lower than the active temperature window of traditional vanadium-titanium catalysts, this type of catalyst has a narrow operating temperature window, poor medium and low temperature activity, is not suitable for low-temperature denitrification of flue gas, is not suitable for low-load denitrification of power plants (flue gas temperature below 300℃), and has a large amount of NH3 escape after low-temperature denitrification. Moreover, SO2 in the flue gas will poison and inactivate the catalyst, including physical poisoning caused by ammonium sulfate / ammonium bisulfate deposition and chemical poisoning caused by sulfation of active sites, thereby affecting the working life of the catalyst and the cost of using the catalyst.

[0004] Although some existing low-temperature denitration catalysts have improved their low-temperature denitration performance to a certain extent, their denitration efficiency in the low-temperature range needs to be further improved, and most of them have poor sulfur resistance, which leads to many restrictions on the use of the catalysts. Therefore, it is urgent to develop a denitration catalyst with excellent low-temperature denitration performance and good sulfur resistance. Summary of the invention

[0005] The present invention provides a sulfur-resistant low-temperature carbon-based denitration catalyst and a preparation method and application thereof, so as to solve the defects of the existing method for preparing low-temperature denitration catalyst, such as high active component loading, high chemical reagent consumption, high catalyst preparation process and high cost.

[0006] According to the first aspect of the present invention, the present invention provides a sulfur-resistant low-temperature carbon-based denitrification catalyst, which is a loaded catalyst with modified activated carbon as a carrier and a metal composite oxide as an active component; the metal composite oxide includes MnO2, Fe2O3 and CeO2, wherein the mass percentages of MnO2, Fe2O3 and CeO2 in the total mass of the catalyst are 6.0-8.0%, 0.5-1.5% and 0.3-1.0% respectively.

[0007] In the above scheme, the sulfur-resistant low-temperature carbon-based denitration catalyst of the present invention uses modified activated carbon as a carrier and manganese-iron-cerium composite oxide as an active component. The three are evenly distributed in the modified activated carbon carrier. CeO2 plays a role of oxygen transmission in the catalyst, accelerating the rate of conversion of NO on the catalyst surface to NO2, and NH3 is more likely to react with NO2. Therefore, adding CeO2 to the catalyst can not only improve the activity of the catalyst, but also has the effect of widening the reaction temperature window. Adding Fe elements can increase the number of acid sites and reducing ability on the catalyst surface, promote catalyst activity, and further widen its denitration temperature window. The co-loading of Mn / Fe / Ce can improve the low-temperature activity and sulfur resistance of the catalyst, significantly improve the low-temperature denitration efficiency of the catalyst, and is conducive to extending the service life of the catalyst. The catalyst has a simple component formula and low cost, and is suitable for popularization and application. The catalyst of the present invention has good sulfur resistance, good pore structure, rich oxygen-containing functional groups, recyclable regeneration, and Mn / Fe / Ce active component NO x It has the advantages of excellent reduction performance, and can have a good denitrification effect at low temperature (100-220℃), and realize low-temperature flue gas denitrification of composite carbon-based catalysts in SO2 atmosphere, and the service life of the catalyst is extended. It is suitable for flue gas desulfurization in existing factories in my country, low temperature after dust removal, low-temperature denitrification, etc.

[0008] Furthermore, the mass percentages of MnO2, Fe2O3 and CeO2 in the total mass of the catalyst are 6.3-7.5%, 0.8-1.5% and 0.3-1.0%, preferably 6.5-7.5%, 0.8-1.2% and 0.3-0.8%. Most preferably, the mass percentages of MnO2, Fe2O3 and CeO2 in the catalyst are 7.0%, 1.0% and 0.5%, respectively.

[0009] In the above scheme, by optimizing and controlling the carrier and the loading amount of each active component, the active components have good mutual coordination, so that the denitrification catalyst has the characteristics of high denitrification accuracy, good activity and stability, and renewable recycling. It can inhibit the escape of ammonia and has good durability, which is beneficial to reducing the denitrification operating cost and improving the economy of the denitrification process.

[0010] Further, the activated carbon is coal-based activated carbon or biomass-based activated carbon. Preferably, the activated carbon is biomass-based activated carbon (such as coconut shell activated carbon, fruit shell activated carbon, etc.).

[0011] Preferably, the activated carbon is in the form of at least one of powdered activated carbon, granular activated carbon, honeycomb activated carbon, fibrous activated carbon fiber, and gauze activated carbon cloth. Activated carbon has a rich pore structure, a large specific surface area, and many oxygen-containing active groups on the surface. It is suitable for use as a carrier of active components. It has a strong adsorption capacity for gaseous substances, can prolong the residence time of flue gas inside the catalyst pores, and improve the catalytic denitrification efficiency. Compared with coal-based activated carbon, biomass-based activated carbon is prepared from biomass materials mainly composed of agricultural waste, and has the advantages of wide sources, environmental friendliness, and low cost.

[0012] According to a second aspect of the present invention, the present invention also provides a method for preparing the above-mentioned sulfur-resistant low-temperature carbon-based denitration catalyst, comprising the following steps:

[0013] The activated carbon is oxidized and modified by using an acid solution to obtain modified activated carbon;

[0014] Prepare a precursor mixed solution; the contents of Mn, Fe and Ce in the precursor mixed solution are calculated based on the mass percentages of their corresponding oxides MnO2, Fe2O3 and CeO2 in the catalyst;

[0015] The modified activated carbon is immersed in the precursor mixed solution, and dried to obtain an activated carbon precursor loaded with Mn / Fe / Ce;

[0016] The activated carbon precursor loaded with Mn / Fe / Ce is sequentially calcined in stages in an inert atmosphere and an air atmosphere to obtain a sulfur-resistant low-temperature carbon-based denitration catalyst.

[0017] In the above scheme, the preparation method of the sulfur-resistant low-temperature carbon-based denitrification catalyst of the present invention is to uniformly load the oxides of Mn / Fe / Ce as active components on the modified activated carbon by an impregnation method after oxidative modification of the activated carbon, and prepare a denitrification catalyst by roasting. At the same time, the loading amount of Mn / Fe / Ce and the specific preparation process parameters are optimized and designed. The preparation method has low preparation cost and energy consumption, a wide source of raw materials, and effectively improves the low-temperature denitrification efficiency of the catalyst, ensuring its low-temperature denitrification effect, and is worthy of promotion.

[0018] Furthermore, the specific steps of the oxidative modification are as follows: the activated carbon is crushed and sieved to 25-40 mesh, washed, and then dried at 100-115°C for 18-30h to obtain an activated carbon pretreatment sample; the activated carbon pretreatment sample is impregnated with an acid solution, washed to neutrality, and then dried at 100-115°C for 18-30h to obtain the modified activated carbon.

[0019] In the above scheme, the modified activated carbon is oxidized and modified by an acid solution. The modified activated carbon has a larger specific surface area, increased oxygen-containing functional groups and acid sites on its surface, and enhanced the adsorption capacity of NH3 on its surface and the adsorption of NO x The catalytic activity is beneficial to the full contact of flue gas and the denitrification reaction.

[0020] Further, the acid solution comprises at least one of 5-40wt% nitric acid solution, sulfuric acid solution and hydrochloric acid solution. Preferably, the acid solution is nitric acid solution. More preferably, the acid solution is 40wt% nitric acid solution.

[0021] Furthermore, the conditions for the acid solution immersion are: temperature of 75-90° C., magnetic stirring for 1-2 h, and rotation speed of 700-800 r / min; the weight volume ratio of the activated carbon pretreated sample to the acid solution is 1 g:(5-8) mL.

[0022] In the above scheme, by optimizing the conditions for impregnation with the acid solution and specifically limiting the weight-to-volume ratio of the activated carbon pretreatment sample to the acid solution, the modified activated carbon efficiency can be improved, and modified activated carbon with better performance can be obtained, which is more conducive to the subsequent loading of active ingredients.

[0023] Further, the manganese source of the precursor mixed solution is a 50wt% Mn(NO3)2 solution, the iron source is Fe(NO3)3·9H2O powder, and the cerium source is Ce(NO3)2 powder;

[0024] And / or, the solvent for preparing the precursor mixed solution is deionized water, and the preparation conditions are: room temperature (it should be noted that room temperature generally refers to 20-35° C.), ultrasonic oscillation for 1-2 hours, and ultrasonic power of 450-500W.

[0025] In the above scheme, by selecting a suitable type of metal source and optimizing the conditions for preparing the precursor mixed solution, it is more conducive to the loading of active ingredients on the modified activated carbon and is beneficial to the improvement of catalyst performance.

[0026] Furthermore, the preparation process of the activated carbon precursor loaded with Mn / Fe / Ce is as follows: using the equal volume impregnation method, taking the modified activated carbon and immersing it in the precursor mixed solution, after magnetic stirring at a speed of 700-800r / min at room temperature for 16-24h, placing it in an oven at 100-115°C for 18-30h to obtain the activated carbon precursor loaded with Mn / Fe / Ce.

[0027] Furthermore, the specific steps of calcining the activated carbon precursor loaded with Mn / Fe / Ce in an inert atmosphere and an air atmosphere in sequence are as follows: placing the activated carbon precursor in a horizontal tube furnace, and under the condition of continuously introducing 180-250 mL / min of inert gas, raising the furnace temperature from room temperature to 400-410°C at a heating rate of 4-8°C / min, and calcining at a constant temperature of 400-410°C for 3.5-4.5 hours, stopping heating, and when the furnace temperature drops below 200°C, switching the inert gas to an air atmosphere of 180-250 mL / min, and continuing to calcine at a constant temperature of 200-210°C for 2-3 hours, naturally cooling to room temperature, and passing through a 25-40 mesh sieve to obtain a high sulfur resistance and low temperature carbon-based denitrification catalyst.

[0028] In the above scheme, by calcining the prepared and dried activated carbon precursor, the components can be better coordinated during the calcination process, and the calcined Fe, Mn and Ce elements are mainly Fe 3+ , Mn 3+ and Mn 4+ 、Ce 4+ The valence state exists on the surface of activated carbon, which helps to further ensure its low-temperature denitration effect. In addition, the introduction of O2 and H2O in the calcination atmosphere can increase the specific surface area and pore volume of the catalyst. The reducibility, acidity, and chemical adsorption oxygen content of the catalyst increase with the increase of O2 content in the calcination atmosphere, and the denitration performance also improves accordingly.

[0029] Furthermore, the inert gas is at least one of nitrogen and argon.

[0030] Furthermore, the air atmosphere contains water vapor in a volume fraction of 0.1-2% (preferably 1.0-1.5%).

[0031] It should be noted that, in the air atmosphere at this time, the volume fraction of O2 remains unchanged, with N2 as the balance gas.

[0032] The inventors found in production and application that under actual working conditions, the denitration catalyst will oxidize SO2 in the flue gas into SO3, and SO3 will further react with NH3 in the flue gas to generate NH4HSO4. The viscous NH4HSO4 will block the pores of the catalyst and cover the active center of the catalyst, causing the catalyst to deactivate, and this inhibition is irreversible. Therefore, controlling the SO2 / SO3 conversion rate of the catalyst is one of the key factors to extend the operating life of the denitration catalyst. The water content in the calcination atmosphere significantly affects the SO2 / SO3 conversion rate under actual operating conditions. When the water content in the calcination atmosphere is low, although the SO2 / SO3 conversion rate is also low, the denitrification efficiency is relatively low. When the water content in the calcination atmosphere is high, although the denitrification efficiency is high, the SO2 / SO3 conversion rate is also high. Therefore, while taking into account both the denitrification efficiency and the SO2 / SO3 conversion rate, it is preferred that the calcination air atmosphere contain 0.1-2% water vapor by volume, which can inhibit the conversion and adsorption of sulfur dioxide on the catalyst surface, effectively prolong the operating life of the denitrification catalyst and reduce its operating cost.

[0033] According to the third aspect of the present invention, the present invention also provides an application of a sulfur-resistant low-temperature carbon-based denitrification catalyst in an SCR denitrification system of low-temperature flue gas, wherein the catalyst is the above-mentioned catalyst or a catalyst prepared by the above-mentioned preparation method; the temperature range of the low-temperature flue gas is 100-220°C.

[0034] The catalyst of the present invention has high sulfur resistance and denitrification activity, and the nitrogen oxide conversion rate can reach more than 91% in the range of 100-220°C. It has high denitrification purification efficiency for low-temperature flue gas, has strong anti-toxic ability for sulfur dioxide present in the flue gas, can inhibit the escape of ammonia, can be recycled, has high durability, and has significant energy-saving and environmental protection benefits for low-temperature denitrification.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] 1) The active components of the sulfur-resistant low-temperature carbon-based denitration catalyst of the present invention are evenly distributed in the activated carbon carrier, and the active components cooperate with each other, so that the denitration window temperature of the catalyst is relatively wide (100-220°C), the denitration performance is stable, the denitration efficiency is high, and the conversion and adsorption of sulfur dioxide on the catalyst surface can be inhibited at the same time. The sulfur resistance is good, and the composite carbon-based catalyst can realize low-temperature flue gas denitration in a SO2 atmosphere, and can be recycled and regenerated. The denitration catalyst has a long service life and low operating cost.

[0037] 2) The preparation method of the sulfur-resistant low-temperature carbon-based denitrification catalyst of the present invention is simple, the raw materials are easily available, the preparation cost is low, and no other impurities appear in the preparation process. By optimizing the control of the carrier and the loading amount of each active component, the activated carbon is modified by oxidation with an acid solution, and the means of staged calcination in a medium-temperature inert atmosphere and a low-temperature air atmosphere are combined to effectively improve the microscopic pore structure of the activated carbon, the number and quality of active sites, which is beneficial to the loading of the Fe / Mn / Ce active components, and makes the loading of the Fe / Mn / Ce active components more uniform, and at the same time enhances the activated carbon's NO x and NH3 adsorption, thereby improving the denitrification efficiency, and also providing the necessary conditions for high denitrification efficiency, high N2 selectivity and sulfur resistance.

[0038] 3) The sulfur-resistant low-temperature carbon-based denitration catalyst of the present invention can be used in a low-temperature flue gas SCR denitration system with a temperature range of 100-220°C, and can achieve the low-temperature and high-efficiency flue gas denitration performance of the Mn / Fe / Ce composite carbon-based catalyst. When the ammonia-nitrogen ratio is 1 and the reaction temperature is 100°C, the denitration activity can reach more than 91%, the denitration efficiency at 130-220°C is as high as more than 98%, and the denitration efficiency at 130°C is as high as 99%. The denitration efficiency at 100°C is increased by more than 10% compared with the Ce / Mn iron-based catalyst; when the reaction temperature is 180°C, under the condition of 30-150ppm SO2, the denitration efficiency is basically not affected within 1h, and under the condition of 90ppm SO2, the denitration efficiency is still maintained at more than 88% after continuous operation for 8h. Compared with the existing 10Fe3Mn / AC catalyst, it has good denitration stability, low sulfur resistance, environmental protection, economy and industrial engineering application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0040] Figure 1 It is a schematic diagram showing the effect of reaction temperature (100-220°C) on the denitration efficiency of the sulfur-resistant low-temperature carbon-based denitration catalyst of Examples 3, 4 and 5 of the present invention when the ammonia-nitrogen ratio is 1 and there is no SO2.

[0041] Figure 2 It is a schematic diagram showing the effect of SO2 concentration (0 ppm, 30 ppm, 90 ppm, 150 ppm) on the denitration efficiency of the sulfur-resistant low-temperature carbon-based denitration catalyst of Example 3 of the present invention when the ammonia-nitrogen ratio is 1 and the reaction temperature is 180°C.

[0042] Figure 3 It is a schematic diagram showing the effect of the presence or absence of SO2 on the continuous reaction denitration efficiency of the sulfur-resistant low-temperature carbon-based denitration catalyst of Example 3 of the present invention when the ammonia-nitrogen ratio is 1 and the reaction temperature is 180°C.

[0043] Figure 4 It is a SEM-Mapping characterization diagram of the fresh denitration catalyst obtained in Example 3 of the present invention under different denitration conditions. DETAILED DESCRIPTION

[0044] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] The following examples use conventional instruments and equipment in the art. Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources, and their specifications are conventional specifications in the art. If no specific techniques or conditions are specified in the following examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0046] It should be noted that, in the present invention and the following embodiments, concentrations, ratios, etc. not otherwise specified are all weight concentrations, weight ratios, etc., "%" means weight percentage, and "parts" means parts by weight, which are common writing habits used by those skilled in the art and will not be described in detail in the present invention.

[0047] As a preferred embodiment, a method for preparing a sulfur-resistant low-temperature carbon-based denitration catalyst of the present invention comprises the following steps:

[0048] 1) The activated carbon was crushed and sieved to 25-40 mesh, washed with deionized water for 3-4 times, and then dried in an oven at 100-115°C for 18-30 hours to obtain an activated carbon pretreatment sample.

[0049] 2) The activated carbon pretreatment sample is impregnated with an acid solution in a constant temperature water bath at a temperature of 75-90°C, magnetically stirred at a speed of 700-800 r / min for 1-2 hours, then washed with deionized water until neutral, and then placed in an oven at 100-115°C for 18-30 hours to obtain modified activated carbon. The weight volume ratio of the activated carbon pretreatment sample to the acid solution is 1g:(5-8)mL.

[0050] The acid solution comprises at least one of 5-40wt% nitric acid solution, sulfuric acid solution and hydrochloric acid solution. Preferably, the acid solution is nitric acid solution. More preferably, the acid solution is 40wt% nitric acid solution.

[0051] 3) According to the equal volume impregnation method, calculate and weigh 50wt% Mn(NO3)2 solution, Fe(NO3)3•9H2O powder and Ce(NO3)2 powder, add deionized water, and ultrasonically vibrate for 1-2h at room temperature and an ultrasonic power of 450-500W to prepare a precursor mixed solution containing Mn / Fe / Ce. The contents of Mn, Fe and Ce in the above precursor mixed solution are calculated based on the mass percentages of their corresponding oxides MnO2, Fe2O3 and CeO2 in the catalyst.

[0052] 4) An equal volume of modified activated carbon is immersed in the precursor mixed solution, and after magnetic stirring at a speed of 700-800 r / min at room temperature for 16-24 hours, it is placed in an oven at 100-115° C. and dried for 18-30 hours to obtain an activated carbon precursor loaded with Mn / Fe / Ce.

[0053] 5) The activated carbon precursor is placed in a horizontal tube furnace, and the furnace temperature is raised from room temperature to 400-410°C at a heating rate of 4-8°C / min while continuously introducing 180-250 mL / min of inert gas, and calcined at 400-410°C for 3.5-4.5 hours. The inert gas is at least one of nitrogen and argon.

[0054] 6) Stop heating the horizontal tube furnace, and when the furnace temperature drops below 200°C, switch the inert gas to an air atmosphere of 180-250mL / min, and continue calcining at 200-210°C for 2-3h, then cool naturally to room temperature, and pass through a 25-40 mesh sieve to obtain a high sulfur resistance and low temperature carbon-based denitrification catalyst. The air atmosphere contains 0.1-2% water vapor by volume.

[0055] In the present invention, the usage amount and ratio of the modified activated carbon and the precursor mixed solution are calculated and weighed according to the equal volume impregnation method in the prior art. Moreover, the room temperature refers to 20-35°C.

[0056] The activated carbon used in the following examples and comparative examples is coconut shell charcoal. The method for calculating the amount of Mn / Fe / Ce precursor contained in step 3) of the following examples is based on 7%Mn1%Fe0.5%Ce / AC as an example: First, calculate the required mass of the precursor: Assuming that the catalyst sample is Yg, the masses of MnO2, Fe2O3 and CeO2 in the catalyst sample are 7.0%Y, 1.0%Y, and 0.5%Y, respectively. Then, the masses of the required 50wt.% Mn(NO3)2 solution, Fe(NO3)3·9H2O powder and Ce(NO3)2 powder are 7.0%Y, respectively. 358 / 87, 1.0%Y 404 / 320 and 0.5%Y 326 / 172.

[0057] Embodiment 1:

[0058] A sulfur-resistant, low-temperature carbon-based denitrification catalyst, which is a supported catalyst with modified activated carbon as a carrier and metal composite oxides as active components; the metal composite oxides include MnO2, Fe2O3 and CeO2, wherein the mass percentages of MnO2, Fe2O3 and CeO2 in the total mass of the catalyst are 6.3%, 1.5% and 1.0% respectively.

[0059] The preparation method comprises the following steps:

[0060] 1) The activated carbon was crushed and sieved to 25-40 mesh, washed with deionized water for 3-4 times, and then dried in an oven at 100°C for 30 hours to obtain an activated carbon pretreatment sample.

[0061] 2) The activated carbon pretreatment sample is impregnated with an acid solution in a constant temperature water bath at 75°C, magnetically stirred at a speed of 700r / min for 2h, washed with deionized water until neutral, and then placed in an oven at 100°C for 30h to obtain modified activated carbon. The weight volume ratio of the activated carbon pretreatment sample to the acid solution is 1g:5mL. The acid solution is a sulfuric acid solution.

[0062] 3) According to the equal volume impregnation method, 5.18g of 50wt% Mn(NO3)2 solution, 0.76g of Fe(NO3)3·9H2O powder and 0.38g of Ce(NO3)2 powder were calculated and weighed, deionized water was added, and ultrasonic vibration was performed for 2h at room temperature and an ultrasonic power of 450W to prepare a precursor mixed solution containing Mn / Fe / Ce. The contents of Mn, Fe and Ce in the above precursor mixed solution were calculated based on the mass percentages of their corresponding oxides MnO2, Fe2O3 and CeO2 in the catalyst of 6.3%, 1.5% and 1.0%, respectively.

[0063] 4) Take 18.24 g of modified activated carbon, immerse an equal volume of it in the precursor mixed solution, stir it magnetically at 700 r / min at room temperature for 24 hours, and then dry it in an oven at 100°C for 30 hours to obtain an activated carbon precursor loaded with Mn / Fe / Ce.

[0064] 5) The activated carbon precursor was placed in a horizontal tube furnace, and the furnace temperature was raised from room temperature to 400°C at a heating rate of 4°C / min while continuously introducing 180 mL / min of inert gas, and calcined at 400°C for 3.5 h. The inert gas was nitrogen.

[0065] 6) Stop heating the horizontal tube furnace, and when the furnace temperature drops below 200°C, switch the inert gas to an air atmosphere at 180 mL / min, and continue calcining at 200°C for 2 hours, then cool naturally to room temperature and pass through a 25-40 mesh sieve to obtain 20 g of a high sulfur resistance, low temperature carbon-based denitration catalyst. The air atmosphere contains 0.1% water vapor by volume.

[0066] Embodiment 2:

[0067] The present embodiment provides a sulfur-resistant, low-temperature carbon-based denitrification catalyst, which is a supported catalyst with modified activated carbon as a carrier and a metal composite oxide as an active component; the metal composite oxide includes MnO2, Fe2O3 and CeO2, wherein the mass percentages of MnO2, Fe2O3 and CeO2 in the total mass of the catalyst are 7.3%, 1.2% and 0.4% respectively.

[0068] The preparation method comprises the following steps:

[0069] 1) The activated carbon was crushed and sieved to 25-40 mesh, washed with deionized water for 3-4 times, and then dried in an oven at 115°C for 18 hours to obtain an activated carbon pretreatment sample.

[0070] 2) The activated carbon pretreatment sample was impregnated with an acid solution in a constant temperature water bath at 90°C, magnetically stirred at 800r / min for 1h, washed with deionized water until neutral, and then dried in an oven at 115°C for 18h to obtain modified activated carbon. The weight-to-volume ratio of the activated carbon pretreatment sample to the acid solution was 1g:8mL. The acid solution was a 40wt% nitric acid solution.

[0071] 3) According to the equal volume impregnation method, 4.51g of 50wt% Mn(NO3)2 solution, 0.46g of Fe(NO3)3·9H2O powder and 0.11g of Ce(NO3)2 powder were calculated and weighed, deionized water was added, and ultrasonic vibration was performed for 1h at room temperature and an ultrasonic power of 500W to prepare a precursor mixed solution containing Mn / Fe / Ce. The contents of Mn, Fe and Ce in the above precursor mixed solution were calculated based on the mass percentages of their corresponding oxides MnO2, Fe2O3 and CeO2 in the catalyst of 7.3%, 1.2% and 0.4%, respectively.

[0072] 4) Take 13.66 g of modified activated carbon, immerse an equal volume of it in the precursor mixed solution, stir it magnetically at 800 r / min at room temperature for 16 h, and then dry it in an oven at 115°C for 18 h to obtain an activated carbon precursor loaded with Mn / Fe / Ce.

[0073] 5) The activated carbon precursor was placed in a horizontal tube furnace, and the furnace temperature was raised from room temperature to 410°C at a heating rate of 8°C / min while continuously introducing 250 mL / min of inert gas, and calcined at 410°C for 4.5 h. The inert gas was nitrogen.

[0074] 6) Stop heating the horizontal tube furnace, and when the furnace temperature drops below 200°C, switch the inert gas to an air atmosphere at 250 mL / min, and continue calcining at 210°C for 3 hours, then cool naturally to room temperature and pass through a 25-40 mesh sieve to obtain 15 g of a high sulfur resistance, low temperature carbon-based denitration catalyst. The air atmosphere contains 1.5% water vapor by volume.

[0075] Embodiment 3:

[0076] The present embodiment provides a sulfur-resistant, low-temperature carbon-based denitrification catalyst, which is a supported catalyst with modified activated carbon as a carrier and a metal composite oxide as an active component; the metal composite oxide includes MnO2, Fe2O3 and CeO2, wherein the mass percentages of MnO2, Fe2O3 and CeO2 in the total mass of the catalyst are 7.0%, 1.0% and 0.5% respectively.

[0077] The preparation method comprises the following steps:

[0078] 1) The activated carbon was crushed and sieved to 25-40 mesh, washed with deionized water for 3-4 times, and then dried in an oven at 105°C for 24 hours to obtain an activated carbon pretreatment sample.

[0079] 2) The activated carbon pretreatment sample was impregnated with an acid solution in a constant temperature water bath at 80°C, magnetically stirred at a speed of 750r / min for 1.5h, washed with deionized water until neutral, and then placed in an oven at 105°C for 24h to obtain modified activated carbon. The weight volume ratio of the activated carbon pretreatment sample to the acid solution was 1g:6mL. The acid solution was a 40wt% nitric acid solution.

[0080] 3) According to the equal volume impregnation method, 3.46g of 50wt% Mn(NO3)2 solution, 0.30g of Fe(NO3)3·9H2O powder and 0.11g of Ce(NO3)2 powder were calculated and weighed, deionized water was added, and ultrasonic vibration was performed for 1.5h at room temperature and an ultrasonic power of 480W to prepare a precursor mixed solution containing Mn / Fe / Ce. The contents of Mn, Fe and Ce in the above precursor mixed solution were calculated based on the mass percentages of their corresponding oxides MnO2, Fe2O3 and CeO2 in the catalyst of 7.0%, 1.0% and 0.5%, respectively.

[0081] 4) Take 10.98 g of modified activated carbon, immerse an equal volume of it in the precursor mixed solution, stir it magnetically at 750 r / min at room temperature for 20 h, and then dry it in an oven at 105°C for 24 h to obtain an activated carbon precursor loaded with Mn / Fe / Ce.

[0082] 5) The activated carbon precursor was placed in a horizontal tube furnace, and the furnace temperature was raised from room temperature to 400°C at a heating rate of 5°C / min while continuously introducing 200 mL / min of inert gas, and calcined at 400°C for 4 hours. The inert gas was nitrogen.

[0083] 6) Stop heating the horizontal tube furnace, and when the furnace temperature drops below 200°C, switch the inert gas to an air atmosphere at 200mL / min, and continue calcining at 200°C for 2h, then cool naturally to room temperature, and pass through a 25-40 mesh sieve to obtain 12g of a high sulfur resistance, low temperature carbon-based denitration catalyst 7Mn1Fe0.5Ce / Ac. The air atmosphere contains 1.0% water vapor by volume.

[0084] Embodiment 4:

[0085] This embodiment provides a sulfur-resistant low-temperature carbon-based denitrification catalyst, which is different from Example 3 in that the mass percentages of MnO2, Fe2O3 and CeO2 in the total mass of the catalyst are 6%, 0.5% and 0.3% respectively.

[0086] The preparation method thereof is different from that of Example 3 in that, in step 3), according to the equal volume impregnation method, 2.96 g of 50 wt.% Mn(NO3)2 solution, 0.076 g of Fe(NO3)3·9H2O powder and 0.068 g of Ce(NO3)2 powder are calculated and weighed, deionized water is added, and ultrasonic oscillation is performed for 1.5 h at room temperature and an ultrasonic power of 480 W to prepare a precursor mixed solution containing Mn / Fe / Ce.

[0087] Embodiment 5:

[0088] This embodiment provides a sulfur-resistant low-temperature carbon-based denitrification catalyst, which is different from Example 3 in that the mass percentages of MnO2, Fe2O3 and CeO2 in the total mass of the catalyst are 7%, 1.5% and 1% respectively.

[0089] The preparation method thereof is different from that of Example 3 in that, in step 3), according to the equal volume impregnation method, 3.46 g of 50 wt.% Mn(NO3)2 solution, 0.227 g of Fe(NO3)3·9H2O powder and 0.227 g of Ce(NO3)2 powder are calculated and weighed, deionized water is added, and ultrasonic oscillation is performed for 1.5 h at room temperature and an ultrasonic power of 480 W to prepare a precursor mixed solution containing Mn / Fe / Ce.

[0090] Comparative Example 1:

[0091] This comparative example provides a sulfur-resistant low-temperature carbon-based denitration catalyst, and its preparation method comprises the following steps:

[0092] 1) is consistent with step 1) of Example 3;

[0093] 2) is consistent with step 2) of Example 3;

[0094] 3) is consistent with step 3) of Example 3;

[0095] 4) is consistent with step 4) of Example 3;

[0096] 5) is consistent with step 5) of Example 3;

[0097] 6) Stop heating the horizontal tube furnace, and when the furnace temperature drops below 200°C, switch the inert gas to an air atmosphere at 200mL / min, and continue calcining at 200°C for 2h, then cool naturally to room temperature, and pass through a 25-40 mesh sieve to obtain 12g of sulfur-resistant low-temperature carbon-based denitration catalyst 7Mn1Fe0.5Ce / Ac. The air atmosphere contains 0.1% water vapor by volume.

[0098] Comparative Example 2:

[0099] This comparative example provides a sulfur-resistant low-temperature carbon-based denitration catalyst, and its preparation method comprises the following steps:

[0100] 1) is consistent with step 1) of Example 3;

[0101] 2) is consistent with step 2) of Example 3;

[0102] 3) is consistent with step 3) of Example 3;

[0103] 4) is consistent with step 4) of Example 3;

[0104] 5) is consistent with step 5) of Example 3;

[0105] 6) Stop heating the horizontal tube furnace, and when the furnace temperature drops below 200°C, switch the inert gas to an air atmosphere at 200mL / min, and continue calcining at 200°C for 2h, then cool naturally to room temperature, and pass through a 25-40 mesh sieve to obtain 12g of a high sulfur resistance, low temperature carbon-based denitration catalyst 7Mn1Fe0.5Ce / Ac. The air atmosphere contains 2.5% water vapor by volume.

[0106] Comparative Example 3:

[0107] This comparative example provides a sulfur-resistant low-temperature carbon-based denitration catalyst, and its preparation method comprises the following steps:

[0108] 1) is consistent with step 1) of Example 3;

[0109] 2) is consistent with step 2) of Example 3;

[0110] 3) is consistent with step 3) of Example 3;

[0111] 4) is consistent with step 4) of Example 3;

[0112] 5) is the same as step 5) of Example 3; and the horizontal tube furnace stops heating, the furnace temperature is cooled naturally to room temperature, and sieved through a 25-40 mesh sieve to obtain 12g of high sulfur resistance and low temperature carbon-based denitration catalyst 7Mn1Fe0.5Ce / Ac. That is, in this comparative example, only nitrogen calcination was used in the calcination stage, and no air atmosphere calcination was used.

[0113] Comparative Example 4:

[0114] This comparative example provides a sulfur-resistant low-temperature carbon-based denitration catalyst, and its preparation method comprises the following steps:

[0115] 1) is consistent with step 1) of Example 3;

[0116] 2) is consistent with step 2) of Example 3;

[0117] 3) is consistent with step 3) of Example 3;

[0118] 4) is consistent with step 4) of Example 3;

[0119] 5) is consistent with step 5) of Example 3;

[0120] 6) The horizontal tube furnace stopped heating, and when the furnace temperature dropped below 200°C, a nitrogen atmosphere of 200 mL / min was continuously introduced, and the calcination was continued at 200°C for 2 hours, and then naturally cooled to room temperature, and passed through a 25-40 mesh sieve to obtain 12 g of a high sulfur resistance and low temperature carbon-based denitration catalyst 7Mn1Fe0.5Ce / Ac. That is, the staged calcination in this comparative example only used nitrogen calcination.

[0121] Comparative Example 5:

[0122] This comparative example provides a low-temperature SCR denitration catalyst, and its preparation method comprises the following steps:

[0123] 1) Add ferric nitrate nonahydrate, cerium nitrate hexahydrate and manganese nitrate into a container at the same time, dissolve them with 88 parts of anhydrous ethanol, place the container in a magnetic stirrer at a speed of 1000 r / min and stir at 25°C for 30 minutes, add nitric acid dropwise until the pH value is 1, prepare solution A, and then ultrasonically vibrate for 1 hour; the ion molar ratio of iron salt, manganese salt and cerium salt after dissolution is 1:0.2:0.6;

[0124] 2) Pour 21 parts of 1 mol / L citric acid into a container, add 88 parts of anhydrous ethanol to dissolve, place the container in a magnetic stirrer at a speed of 1000 r / min and stir at 25°C for 30 minutes to prepare solution B;

[0125] 3) Slowly and evenly add 100 parts of solution B to 100 parts of solution A which is continuously stirred to obtain a mixed solution C, place solution C in a constant temperature oil bath magnetic stirrer, stir at 25°C for 30 minutes at a speed of 1000 r / min to obtain a transparent sol;

[0126] 4) reflux the transparent sol obtained in step 3) at 60° C. for 7 h using a spiral condenser to obtain a wet gel;

[0127] 5) The wet gel obtained in step 4) was dried in an electric blast drying oven at 105°C for 24 hours, transferred to a muffle furnace and heated to 400°C at 2°C / min for calcination, calcined and kept warm for 6 hours, ground and passed through a 40-mesh sieve to obtain a low-temperature denitration catalyst Ce / Mn iron-based catalyst for flue gas denitration.

[0128] Comparative Example 6:

[0129] The present comparative example provides a low-temperature SCR denitration catalyst, and the preparation method thereof comprises the following steps: drying an activated carbon carrier at 105°C for 4 hours, then grinding the dried activated carbon to 50 mesh to obtain small carrier particles, using the ground activated carbon particles as a carrier, and loading the active components on the carrier by an impregnation method, first weighing a certain weight of the activated carbon carrier, and then calculating the mass of ferric nitrate and manganese nitrate solutions to be weighed based on the Fe loading being 10% of the weight of the activated carbon carrier, the Mn loading being 3% of the weight of the activated carbon carrier, and the law of conservation of elements, and then pouring them into a beaker loaded with the activated carbon carrier in turn, adding deionized water, and after being fully stirred for 10 hours with a magnetic stirrer, placing the catalyst in a 105°C forced air drying oven and drying it for 10 hours, and finally calcining it at 400°C in a closed air atmosphere for 5 hours, and then cooling it with the furnace to obtain a catalyst, which is marked as 10Fe3Mn / AC.

[0130] Test Example 1:

[0131] Catalyst performance evaluation: The catalysts prepared in Examples 1 to 3 and Comparative Examples 1 to 6 of the same weight were taken as test samples, and their denitration performance and SO2 / SO3 conversion rate were tested. To ensure the reliability of the test results, each experimental condition was set up with 3 parallels, and the test was repeated 3 times, and the average value was taken. The results are shown in Table 1.

[0132] 1) Use a fixed bed micro-reaction evaluation device to test the denitrification performance of the catalyst. Catalyst loading 0.5mL, volume space velocity 120000h -1 . Test flue gas conditions: 0.05% NO, 0.05% NH3, 5% O2, N2 as balance gas. Test temperature is 150℃. During the test, the catalyst was placed in the denitration reactor for reaction for more than 30 minutes, and the concentration of components in the flue gas was analyzed using the MPO3000 flue gas analyzer of Emerson Company of the United States. The denitration efficiency of the catalyst η / %=(φin-φout) / φin×100%, where φin and φout are the NO inlet and outlet, respectively. x (NO and NO2) volume fraction, %.

[0133] 2) A full-scale denitration catalyst pilot evaluation device was used to analyze and test the catalyst for SO2 conversion to SO3. The formed denitration catalyst (flat plate, 150mm×150mm) was used, and 25 catalyst plates were placed in the reactor. The test conditions were: flue gas flow rate 150m 3 ·h -1, temperature 150℃, 4.25%O2, 15.00%H2O, SO2 content 400ppm, NO content 250ppm, ammonia nitrogen ratio 1, balance gas N2. EcoIC ion chromatograph of Metrohm Company of Switzerland was used to analyze SO3 concentration in flue gas, and MultiGas6030 Fourier transform infrared spectrometer of MKS Company of the United States was used to analyze SO2 concentration in flue gas. The conversion rate of SO2 to SO3 of the catalyst is α / %=(φ1in-φ1out) / φ2in×100%, where φ1in and φ1out are the volume fractions of SO3 at the inlet and outlet, respectively; φ2in is the volume fraction of SO2 at the inlet, %.

[0134] Table 1

[0135]

[0136] By comparing the data of Examples 1 to 3 and Comparative Examples 5 and 6, it is found that the catalyst of the embodiment of the present invention has a higher denitration efficiency at the same flue gas temperature and a lower SO2 / SO3 conversion rate. In the test, it was also found that the denitration efficiency of Comparative Example 5 at a low temperature of 100°C was about 80%, which was lower than the denitration efficiency of more than 91% of the catalyst of the present invention at 100°C, and the denitration efficiency of Comparative Example 6 at a low temperature of 120°C was about 70%, and at 160°C it was about 90%, which was also lower than the denitration efficiency of the catalyst of the present invention at the same temperature. It can be seen that the catalyst of the present invention can show excellent denitration performance and sulfur resistance at a lower temperature, with a wider temperature window and a wider range of application, and has significant advantages.

[0137] By comparing the data of Example 3 and Comparative Examples 3 and 4, it is found that the staged calcination method in Example 3 through medium-temperature inert atmosphere and low-temperature air atmosphere effectively improves the denitrification efficiency, high N2 selectivity and sulfur resistance. Therefore, the staged calcination method in the present invention can further improve the various performances of the denitrification catalyst.

[0138] By comparing the data of Example 3 with Comparative Examples 1 and 2, it is found that, compared with Example 3, when the water content in the calcination atmosphere of Comparative Example 1 is low, although the SO2 / SO3 conversion rate is also low, there is also a relatively low denitration efficiency. When the water content in the calcination atmosphere of Comparative Example 3 is high, although the denitration efficiency is high, the SO2 / SO3 conversion rate is also high. Therefore, in the case of taking into account both the denitration efficiency and the SO2 / SO3 conversion rate, preferably, the natural air for calcination of the present invention contains 0.1-2% water vapor by volume, which can inhibit the conversion and adsorption of sulfur dioxide on the catalyst surface, effectively prolong the operating life of the denitration catalyst and reduce its operating cost.

[0139] Test Example 2:

[0140] Low-temperature denitration performance test: The catalysts prepared in Examples 3-5 were taken as test samples to test their low-temperature denitration efficiency. To ensure the reliability of the test results, each experimental condition was set up with 3 parallels, and the test was repeated 3 times to take the average value. The specific test steps are: the prepared catalyst was placed in a quartz tube of a vertical fixed bed reactor for testing, wherein the simulated flue gas concentrations were: NO was 400ppm, NH3 was 400ppm, O2 was 6vol%, CO2 was 12vol%, N2 was the balance gas, and the gas flow rate was 2L / min; the reaction temperature was 100-220°C, and the volume space velocity was 10000h -1 At different temperatures (100°C, 130°C, 160°C, 190°C, 220°C), the denitration efficiency of the denitration catalyst prepared in this embodiment is as follows: Figure 1 As shown. The results show that when the reaction temperature is 100°C, the denitration activity of the sulfur-resistant low-temperature carbon-based denitration catalyst of Example 3 can reach 91.6%, the denitration efficiency at 130-220°C is as high as more than 98%, and the denitration efficiency at 130°C is as high as 99%, showing high denitration efficiency and excellent denitration performance. When the reaction temperature is 130-220°C, the denitration activity of the sulfur-resistant low-temperature carbon-based denitration catalyst of Example 4 can reach more than 90%, and the denitration activity of the sulfur-resistant low-temperature carbon-based denitration catalyst of Example 5 remains above 95%, and the effects are not as good as the sulfur-resistant low-temperature carbon-based denitration catalyst of Example 3.

[0141] Test Example 3:

[0142] Anti-sulfur performance test: The catalyst prepared in Example 3 was taken as the test sample to test its low-temperature anti-sulfur performance. To ensure the reliability of the test results, each experimental condition is set up with 3 parallels, and the test is repeated 3 times to take the average value. The specific test steps are: put the prepared catalyst into a quartz tube of a vertical fixed bed reactor for testing, wherein the simulated flue gas concentrations are: NO is 400ppm, NH3 is 400ppm, SO2 concentration is 0-150ppm, O2 is 6vol%, CO2 is 12vol%, N2 is the balance gas, and the gas flow rate is 2L / min; the reaction temperature is 180°C, and the volume space velocity is 10000h -1 The effect of SO2 concentration on the denitration efficiency of the catalyst of Example 3 was tested at different SO2 concentrations (0 ppm, 30 ppm, 90 ppm, 150 ppm). The results are as follows: Figure 2 shown.

[0143] Figure 2The figure is a schematic diagram showing the effect of SO2 concentration (0ppm, 30ppm, 90ppm, 150ppm) on the denitration efficiency of the sulfur-resistant low-temperature carbon-based denitration catalyst of Example 3 when the ammonia nitrogen ratio is 1 and the reaction temperature is 180°C. The results show that under the condition of 30-150ppm SO2, the denitration efficiency is basically not affected within 1h of reaction, and the denitration efficiency is always maintained at more than 99%, indicating that the denitration catalyst of this example and the present invention has excellent sulfur resistance.

[0144] Test example 4:

[0145] Continuous anti-sulfur performance test: The catalyst prepared in Example 3 was taken as the test sample to test its low-temperature anti-sulfur performance. To ensure the reliability of the test results, each experimental condition is set up with 3 parallels, and the test is repeated 3 times to take the average value. The specific test steps are: put the prepared catalyst into a quartz tube of a vertical fixed bed reactor for testing, wherein the simulated flue gas concentrations are: NO is 400ppm, NH3 is 400ppm, SO2 concentration is 0ppm or 90ppm, O2 is 6vol%, CO2 is 12vol%, N2 is the balance gas, and the gas flow rate is 2L / min; the reaction temperature is 180°C, and the volume space velocity is 10000h -1 The denitrification efficiency under long-term operation is as follows Figure 3 At the same time, the surface morphology and element distribution of the materials before and after denitration in the above test example were analyzed by field emission scanning electron microscope-energy spectrometer (SEM-EDS, FEI TecnaiG2F30), and the SEM-Mapping characterization diagram of the catalyst obtained by the test was as follows: Figure 4 shown.

[0146] Figure 3 The figure is a schematic diagram showing the effect of the presence or absence of SO2 on the continuous reaction denitration efficiency of the sulfur-resistant low-temperature carbon-based denitration catalyst of Example 3 when the ammonia nitrogen ratio is 1 and the reaction temperature is 180°C. The results show that the denitration efficiency of the catalyst of Example 3 is higher than 98% within 10 hours in the presence of 0ppm SO2; in the presence of 90ppm SO2, continuous operation for 5.5 hours has basically no effect on its denitration performance, and can still be maintained at more than 99%; when it runs for 8 hours, it still maintains a denitration efficiency of more than 88%, indicating that the catalyst of this example and the present invention has good denitration stability and sulfur resistance.

[0147] Figure 4The SEM-Mapping characterization diagram of the catalyst of Example 3 under different denitration conditions. SEM analysis shows that the surface of the fresh catalyst loaded with Mn, Fe, and Ce is dense, and its surface pores are mainly small pores, and the microscopic pore structure has also been significantly improved. The O element on the surface of the fresh catalyst can be seen from the mapping photo of the catalyst surface. It can be observed that the O element is obvious and evenly distributed on the surface of the fresh catalyst. The Mn element distribution photo can be observed to be more obvious. The Mn element is evenly distributed in the micropores of the carbon-based catalyst, which helps to increase the number of Mn4+ active sites of the catalyst, thereby enhancing its low-temperature denitration performance. Compared with the fresh catalyst, after reacting under the working conditions of the 0ppm SO2 atmosphere of Test Example 2 and Test Example 4, the catalyst surface is evenly covered with S elements. Similarly, after reacting under the working conditions of the 0ppm SO2 atmosphere of Test Example 3 and Test Example 4, the catalyst surface is also evenly covered with S elements, especially the catalyst surface of the continuous reaction of 90ppm SO2 for 10h in Test Example 4. Due to the longer reaction time, the accumulated amount of S elements is more.

[0148] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A sulfur-resistant low-temperature carbon-based denitration catalyst, characterized in that: The catalyst is a supported catalyst with modified activated carbon as a carrier and metal composite oxide as an active component; the metal composite oxide includes MnO2, Fe2O3 and CeO2, wherein the mass percentages of MnO2, Fe2O3 and CeO2 in the total mass of the catalyst are 6.0-8.0%, 0.5-1.5% and 0.3-1.0% respectively; The method for preparing the sulfur-resistant low-temperature carbon-based denitration catalyst is characterized by comprising the following steps: The activated carbon is oxidized and modified by using an acid solution to obtain modified activated carbon; Prepare a precursor mixed solution; the contents of Mn, Fe and Ce in the precursor mixed solution are calculated based on the mass percentages of their corresponding oxides MnO2, Fe2O3 and CeO2 in the catalyst; The modified activated carbon is immersed in the precursor mixed solution, and dried to obtain an activated carbon precursor loaded with Mn / Fe / Ce; The activated carbon precursor loaded with Mn / Fe / Ce is sequentially calcined in stages in an inert atmosphere and an air atmosphere to obtain a sulfur-resistant low-temperature carbon-based denitration catalyst; The specific steps of calcining the activated carbon precursor loaded with Mn / Fe / Ce in an inert atmosphere and an air atmosphere in sequence are as follows: placing the activated carbon precursor in a horizontal tube furnace, and under the condition of continuously passing an inert atmosphere of 180-250 mL / min, raising the furnace temperature from room temperature to 400-410°C at a heating rate of 4-8°C / min, and calcining at a constant temperature of 400-410°C for 3.5-4.5 hours, stopping heating, and when the furnace temperature drops below 200°C, switching the inert atmosphere to an air atmosphere of 180-250 mL / min, and continuing to calcine at a constant temperature of 200-210°C for 2-3 hours, naturally cooling to room temperature, and passing through a 25-40 mesh sieve to obtain a high sulfur resistance and low temperature carbon-based denitrification catalyst; the inert atmosphere is at least one of nitrogen and argon; the air atmosphere contains water vapor with a volume fraction of 0.1-2%.

2. The sulfur-resistant low-temperature carbon-based denitration catalyst according to claim 1, characterized in that: The mass percentages of MnO2, Fe2O3 and CeO2 in the total mass of the catalyst are 6.3-7.5%, 0.8-1.5% and 0.3-1.0% respectively.

3. The sulfur-resistant low-temperature carbon-based denitration catalyst according to claim 1, characterized in that: The specific steps of the oxidative modification are as follows: crushing the activated carbon and sieving it to 25-40 mesh, washing it, and then drying it at 100-115°C for 18-30h to obtain an activated carbon pretreatment sample; impregnating the activated carbon pretreatment sample with an acid solution, washing it to neutrality, and then drying it at 100-115°C for 18-30h to obtain the modified activated carbon.

4. The sulfur-resistant low-temperature carbon-based denitration catalyst according to claim 3, characterized in that: The conditions for the acid solution immersion are: temperature of 75-90° C., magnetic stirring for 1-2 h, and rotation speed of 700-800 r / min; the weight volume ratio of the activated carbon pretreatment sample to the acid solution is 1 g: (5-8) mL.

5. The sulfur-resistant low-temperature carbon-based denitration catalyst according to claim 1, characterized in that: The manganese source of the precursor mixed solution is 50wt% Mn(NO3)2 solution, the iron source is Fe(NO3)3·9H2O powder, and the cerium source is Ce(NO3)2 powder; And / or, the solvent for preparing the precursor mixed solution is deionized water, and the preparation conditions are: room temperature, ultrasonic oscillation for 1-2 hours, and ultrasonic power of 450-500W.

6. The sulfur-resistant low-temperature carbon-based denitration catalyst according to claim 1, characterized in that: The preparation process of the Mn / Fe / Ce loaded activated carbon precursor is as follows: using an equal volume impregnation method, taking the modified activated carbon and immersing it in a precursor mixed solution, magnetically stirring at a speed of 700-800 r / min at room temperature for 16-24 hours, and then placing it in an oven at 100-115° C. for 18-30 hours to obtain the Mn / Fe / Ce loaded activated carbon precursor.

7. Application of a sulfur-resistant low-temperature carbon-based denitration catalyst in a SCR denitration system for low-temperature flue gas, characterized in that: The catalyst is the catalyst according to any one of claims 1 to 6; the temperature range of the low-temperature flue gas is 100-220°C.

Citation Information

Patent Citations

  • Low-temperature smoke denitration SCR (silicon controlled rectifier) catalyst and preparation method

    CN102114424A

  • SCR (Selective catalytic reduction) monolithic honeycombed catalyst for low-temperature flue gas de-nitrification and preparation method thereof

    CN103464194A

  • Active carbon-based low-temperature SCR denitration catalyst and preparation method thereof

    CN107115868A

  • Low-sulfur-resistant low-temperature carbon-based denitration catalyst as well as preparation method and application thereof

    CN112403488A

  • Low-temperature SCR denitration catalyst and preparation method thereof

    CN113083320A

Cited By

  • Sulfur-resistant ultralow-temperature manganese-based denitration catalyst as well as preparation method and application thereof

    CN120305981A